The effect of the aqueous and alcoholic extracts of Tamarindus indica in suppressing hyperglycaemia in alloxan-induced diabetic rats - Jassim, Suaad Mohsen; Jwad, Saher Mahmood (Pharmakeftiki, 2025)
This study has investigated the antihyperglycaemic effects of aqueous and alcoholic extracts of Tamarindus indica (T. indica) in adult male Sprague Dawley rats with alloxan-induced diabetes. Forty-nine rats (mean body weight: 230 ± 20 g) were randomly assigned to seven groups (n=7 per group): group 1 comprised healthy control rats, group 2 included diabetic control rats, groups 3 and 4 included diabetic rats that received 500 mg/kg of aqueous or alcoholic T. indica extract (orally, via gavage), groups 5 and 6 included non-diabetic (normal) rats that received the same doses of aqueous or alcoholic T. indica extract as the previous two groups; and group 7 included diabetic rats that were treated subcutaneously with insulin (6 IU/kg body weight). Diabetic rats (group 2) exhibited a significant elevation in blood glucose levels (p<0.05), whereas all treatments with T. indica extracts (groups 3–6) resulted in a statistically significant reduction (p<0.05) of the rat blood glucose levels, with the alcoholic extract demonstrating the most pronounced effect. These findings provide evidence of the antihyperglycaemic activity of T. indica, the extracts of which possess potent antioxidant properties and may offer therapeutic benefit in the management of diabetes.